Poly (3,4-ethylenedioxythiophene) (PEDOT) nanofibers decorated graphene oxide (GO) as high-capacity, long cycle anodes for sodium ion batteries - Pu, Zejun (2019)
Conductive Poly (3,4-ethylenedioxythiophene) (PEDOT) nanofibers are uniformly deposited on ultrathin graphene oxide (GO) nanosheets via a simple and effective in situ polymerization process under ambient conditions. The as-prepared samples are characterized by field-emission scanning electron microscopy (FE-SEM), transmission electron microscopy (TEM), Raman spectra, Fourier transforms infrared spectra (FTIR), and electrochemical measurements. The results indicate that the as-obtained PEDOT–GO hybrid (GDOT) achieves excellent sodium storage properties. When explored as a new inorganic/polymeric electrode for sodium ion batteries (SIBs), the GDOT exhibits a high reversible capacity (338 mAh g−1), good cycling stability (234 mAh g−1 after 400 cycles), and excellent rate capabilities (e.g., 62 mAh g−1 at 30 A g−1) due to their ultrathin structure as well as conductive network. This easily scale-up-able and effective strategy shows great potential for large-scale energy applications.